2017
DOI: 10.1248/cpb.c17-00269
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Stratum Corneum Lipid Liposomes for Screening of Chemical Skin Penetration Enhancers

Abstract: The evaluation of effective skin chemical penetration enhancers (CPEs) is a crucial process in the development of transdermal and dermal formulations with the capacity to overcome the stratum corneum barrier. In the present study, we aimed to investigate the potential of stratum corneum lipid liposomes (SCLLs) as an alternative tool for the screening of various types and concentrations of CPEs. SCLLs were prepared using a thin-film hydration technique, and two types of fluorescent probes ( Key words stratum co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
(35 reference statements)
1
4
0
Order By: Relevance
“…Transcutol is needed to increase the efflux to a great extent ( Figure 8B). This finding is in agreement with a previous study [24]. Transcutol is reported to interact with the aqueous domain of the lipid bilayer which increase the solubility of drugs in the skin.…”
Section: Calcein Efflux and Lifetime-based Fluorescence Leakage Assaysupporting
confidence: 94%
See 1 more Smart Citation
“…Transcutol is needed to increase the efflux to a great extent ( Figure 8B). This finding is in agreement with a previous study [24]. Transcutol is reported to interact with the aqueous domain of the lipid bilayer which increase the solubility of drugs in the skin.…”
Section: Calcein Efflux and Lifetime-based Fluorescence Leakage Assaysupporting
confidence: 94%
“…Transcutol, a monoethyl ether of diethylene glycol, is classified into the group of alcohols and glycols, which are reported to interact with the aqueous domain of the lipid bilayers, which increase the solubility of drugs in the skin [24]. Harrison et al reported that the penetration enhancement property of Transcutol is the result of changes in solubility rather than diffusion in the membrane [25].…”
Section: Chemical Penetration Enhancersmentioning
confidence: 99%
“…This finding is in agreement with a previous study. 1 Transcutol is reported to interact in the aqueous domain of the lipid bilayers which increase the solubility of drugs in the skin. According to Moghadam et al , Transcutol caused only a slight disordering effect within the SC membrane.…”
Section: Resultsmentioning
confidence: 99%
“…The skin has been recognized as a highly attractive application site of therapeutic agents with both local and systemic effects. 1 However, the outermost layer of the skin, the stratum corneum (SC) forms a barrier, which makes it hard for active pharmaceutical ingredients (API) to pass through this layer and exert their pharmacological effects. 2 It has been shown that the transdermal flux of API and SC lipid conformation is strongly correlated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation